2005
DOI: 10.1063/1.1903100
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity at room temperature in Pr-doped SrTiO3

Abstract: The influence of Pr ion on the structural and dielectric properties was studied in Sr1−xPrxTiO3 for 0<x<0.075 composition from room temperature to 375°C. X-ray diffraction and x-ray photoelectron spectroscopy studies revealed that the praseodymium ion enters substitutionally in the Sr site with mixed valence in a Pr+3∕Pr+4=2:1 ratio. This substitution yields compressive chemical pressure in the lattice. The polarization measurements at room temperature display hysteresis loops, indicating that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
70
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 17 publications
9
70
2
2
Order By: Relevance
“…This phase could not be accurately identified from the power diffraction database due to the weak intensities of the reflections. The possible secondary phases from the powders diffraction database might be Pr 5 are observed in the praseodymium oxide secondary phase. The inset shows the magnified micrograph of a secondary phase particle possessing a clearly different morphology than the matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase could not be accurately identified from the power diffraction database due to the weak intensities of the reflections. The possible secondary phases from the powders diffraction database might be Pr 5 are observed in the praseodymium oxide secondary phase. The inset shows the magnified micrograph of a secondary phase particle possessing a clearly different morphology than the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…4 The majority of these phenomena were induced (observed) by modification of the perovskite lattice via either creation of oxygen vacancies and/or substitutional doping. Among the variety of dopants used to dope the "STO" lattice, praseodymium-doped STO displayed unique properties such as room-temperature ferroelectricity, 5 colossal dielectric constant, 6 photoluminescence, 7,8 and thermoelectric properties (specifically, a very large thermoelectric power factor). 9,10 The thermoelectric power factor, PF, is a measure of the potential of the electronic transport in a material for thermoelectric applications and is defined herein as PF ¼ a 2 rT, where a is the Seebeck coefficient, r the electrical conductivity, and T the absolute temperature in Kelvin.…”
mentioning
confidence: 99%
“…Stoichiometric ratios of SrCO 3 , TiO 2 , and Pr 6 O 11 , each of purity greater than 99.9% ͑Alpha Aesar͒, were thoroughly mixed and calcined at 1100°C for 3 h. The disk-shaped pellets were sintered at 1300°C for 2 h. It may, however, be mentioned that Pr can exist in 3+ and 4+ valence states, 14 15 a possibility of some fraction of the substituted Pr ions occupying the Ti site is also quite likely. In this paper, we have, however, not concerned ourselves with the problem of site occupancy of the substituted Pr ions in STO.…”
Section: Methodsmentioning
confidence: 99%
“…A possibility of stabilizing the ferroelectric phase at room temperature and above was theoretically predicted for biaxially strained STO 12 and was subsequently realized in a thin STO film grown on a DyScO 3 substrate. 13 Durán et al 14 have recently reported the existence of a ferroelectric phase in Pr-doped SrTiO 3 ceramics even at room temperature. So far no detailed study in this regard has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 STO is also a perfect prototype to investigate phase transition, 3 especially to understand the surface and interface structural configuration for the perovskite films grown on it. 4 Although ferroelectric properties were only reported through oxygen isotope exchange ͑ST 18 O͒, 3,5 and cation substitution, 6,7 recent theories and experiments validate the existence of ferroeletricity in STO thin films under strain. [8][9][10] He et al [11][12][13] systematically studied the structural phase transition of STO thin films under strain.…”
mentioning
confidence: 99%